A Study of Differential Expression of Testicular Genes in Various Reproductive Phases of Hemidactylus flaviviridis (Wall Lizard) to Derive Their Association with Onset of Spermatogenesis and Its Relevance to Mammals - Sarkar, Hironmoy (PLoS One, 2016)
Testis of Hemidactylus flaviviridis, commonly known as Indian wall lizard, displays a lack of cellular and metabolic activity in regressed phase of testis during non-breeding season of the year. Retracted Sertoli cells (Sc), fibroid myoid cells and pre-meiotic resting spermatogonia are observed in such testis. This situation is akin to certain forms of infertility in men where hormone supplementation fails to generate sperm despite the presence of Sc and germ cells (Gc) in testis. In testis of lizard, spermatogenesis is reinitiated upon increased level of hormones during appropriate season (phase of recrudescence). Study of genes associated with generation of sperm, from regressed adult testis in lizard, may provide valuable information for understanding certain forms of male idiopathic infertility. Subtractive hybridization using testicular RNA obtained from the regressed and active phases of lizard reproductive cycle led to identify eight partial mRNA sequences that showed sequence homology with mice genes. We further evaluated the gene expression prolife by real-time PCR in three different reproductive phases of H. flaviviridis: regressed (pre-meiotic), recrudescent (meiotic) and active (post meiotic), for comparison with the corresponding testicular phases found in testis of 5 days (pre-meiotic), 20 days (meiotic) and 60 days (post-meiotic) old mouse. This is the first report where genes associated with progression of spermatogenesis during active phase, which follows a regressed state of adult testis, were identified in lizard and found to be conserved in mouse. Six important genes, Hk1, Nme5, Akap4, Arih1, Rassf7 and Tubb4b were found to be strictly associated with active spermatogenesis in both mouse and lizard. Factors interfering with the expression of any of these genes may potentially abrogate the process of spermatogenesis leading to infertility. Such information may shed light on unknown causes of idiopathic male infertility.